Implementasi K3 dalam Pencegahan Kecelakaan Kerja di Stasiun Pengisian dan Pengangkutan Bulk Elpiji PT X - Elviana Nur Erlinawati; Syefira Ayudia Johar; Nur Ani; Wartini Wartini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Occupational safety and health are important components in high-risk industrial operations. The LPG industry has complex hazard characteristics because LPG is composed of a mixture of hydrocarbons, especially propane and butane, which are flammable and high pressure. This study aims to analyze the implementation of OHS in preventing work accidents at SPPBE PT X. The research method used is a qualitative case study approach, with data collection techniques through observation, interviews, and document review. The results of the study indicate that the implementation of OHS at PT X has been running well, indicated by the existence of OHS policies, work SOPs, safety briefings, OHS training, and the provision of safety facilities and equipment. However, there are still discrepancies in the type of PPE with potential hazards in the LPG industrial environment, non-compliance with the use of PPE, unsafe behavior in the form of work implementation that does not comply with procedures, and unsafe conditions such as rubber carpets on worn and uneven floors, hot working temperatures due to zinc roofs, and rusty or corroded equipment. These findings indicate that the implementation of OHS at SPPBE PT X has been running, but has not been optimal in preventing work accidents. Companies need to improve the suitability of PPE based on hazard identification, strengthen worker compliance monitoring, and carry out work environment control based on the hierarchy of control principle.